Basic in vitro characterization of the vasodilatory potential of 2-aminoethyl nitrate fixed-dose combinations with cilostazol, metoprolol and valsartan - Oelze, Matthias; Scherhag, Armin (Pharmacology, 2018)
Background/Aims: 2-aminoethyl nitrate (CLC-1011) is a member of the class of organic nitrates that cause vasodilation by the generation of nitric oxide (•NO). These drugs are mainly used for the treatment of angina pectoris and ischemic heart disease. The aim of this study was to characterize the vasodilatory potency of this organic nitrate alone and in combination with clinically established cardiovascular drugs. Methods: Vasodilation by CLC-1011 was tested by isometric tension studies, either alone or combined with cilostazol, valsartan, and metoprolol. Induction of oxidative stress in isolated heart mitochondria was measured by enhanced chemiluminescence. Bioactivation of CLC-1011 in aortic tissue was measured by electron paramagnetic resonance spectroscopy using an iron-based spin trap for •NO. Results: We observed potent vasodilation by CLC-1011 and additive effects for all three drug combinations. In contrast to nitroglycerin (GTN), CLC-1011 did not stimulate mitochondrial oxidative stress. CLC-1011 was bioactivated to •NO in aortic tissue. Conclusion: In summary, the experiments described in this report demonstrate that CLC-1011 does not induce oxidative stress, is a more potent vasodilator than isosorbide-5-mononitrate and dinitrate ISDN, and displays synergistic vasodilation with other cardiovascular drugs. CLC-1011 fixed dose combinations could be used in the management of cardiovascular diseases.